2006
DOI: 10.1042/bst0340389
|View full text |Cite
|
Sign up to set email alerts
|

The OSBP-related proteins (ORPs): global sterol sensors for co-ordination of cellular lipid metabolism, membrane trafficking and signalling processes?

Abstract: Protein families related to OSBP (oxysterol-binding protein) are present in eukaryotes from yeast to human. The functions of the ORPs (OSBP-related proteins) have remained largely enigmatic. Even though they have been implicated in the function of ERJs (endoplasmic reticulum junctions), it is evident that any single model for their mechanism of action is insufficient. The existing evidence points in many different directions, such as integration of sterol and sphingomyelin metabolism, regulation of neutral lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
(31 reference statements)
1
38
0
Order By: Relevance
“…We have observed that pharmacologic activators of liver X receptors such as T0901317 stimulate lipogenesis in MCF-7 cells (data not shown), suggesting that they might participate in the breast cell differentiation processes stimulated by AEBS ligands. Alternatively, oxysterols can bind to the oxysterol binding protein (OSBP)-related proteins (32). OSBP-related proteins constitute a family of cytosolic proteins involved in lipid metabolism (33).…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that pharmacologic activators of liver X receptors such as T0901317 stimulate lipogenesis in MCF-7 cells (data not shown), suggesting that they might participate in the breast cell differentiation processes stimulated by AEBS ligands. Alternatively, oxysterols can bind to the oxysterol binding protein (OSBP)-related proteins (32). OSBP-related proteins constitute a family of cytosolic proteins involved in lipid metabolism (33).…”
Section: Discussionmentioning
confidence: 99%
“…The human OSBP family consists of 12 members. OSBP family proteins have an oxysterol binding domain, which binds oxysterol, and a PH domain, which attaches to non-ER membranes via binding of phosphatidylinositol 17,18) . By binding oxysterol or cholesterol, they cause conformational change, and induce signal transduction to regulate cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similar to other members of the OSBP family, OSBPL10 has an oxysterol-binding domain and a PH domain, which attaches to non-ER membranes through binding of phosphatidylinositol. 8,17 The identified cSNP (amino-acid substitution D254N) is located in the hinge region between two domains. This region is required for attachment to some organelles.…”
Section: -3)mentioning
confidence: 99%
“…It has also been implicated in signal transduction, vesicular transport and lipid metabolism. 8,9 Families of proteins with homology to the C-terminal sterol-binding domain of OSBP are present in practically all eukaryotic organisms for which sequence information is available. In human beings, the gene family consists of 12 members, including oxysterol-binding protein-like 10 (OSBPL10).…”
Section: Introductionmentioning
confidence: 99%